UJI BEBERAPA DOSIS KASCING PADA BIBIT KAKAO (Theobroma cacao L.) - Putri Ayu Handayani; Sampoerno '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Cocoa (Theobroma cacao L.) is a plantation crop that has a high economic value, but low productivity and quality of cocoa in Indonesia due to substantial losses. One of many efforts we can do to improve the quality and quantity of cocoa production is through improving the quality of seeds. Fertilizing is one of important factor on the growth of cocoa seedling. Application of organic material as fertilizer can give a good effect for plants. One of many organic material that can be used is a mixture of vermicompost. This study aim is to determine the effectof vermicompost on the growth of cocoa seedlings and get the best doses for the growth of cocoa seedlings. This research was conducted in the experimental field of Agriculture Faculty, University of Riaufrom September to December 2014. This research was carried out using completely randomized design (CRD), which consisted of 4 treatments with 3 replications. The treatments consisted of :(K1) without vermicompost/plant, (K2) 15 gvermicompost/plant, (K3) 25 gvermicompost/plant, (K4) 35 gvermicompost/plant. The results showed that the giving of vermicompost on cocoa seedlings effected on seedling height, number of leaves, girth and leaf area. Giving vermicompost 25 g/plant the best results on the growth of cocoa seedlings.   Keyword: vermicompost, organic material, cocoa seedling